Slujirea pastorală a credincioşilor cu deficienţe de auz şi vorbire din cadrul parohiei deficienţilor de auz şi vorbire „Sfinţii Ierarhi şi Mărturisitori Iorest şi Sava, Mitropoliţii Transilvaniei şi Iosif Episcopul Maramureşului” Cluj-Napoca - Petrescu, Adrian (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2023)
Communication with God as well as communication with others is paramount in accepting difficulties, deficiencies. Man must not be a solitary being, he must overcome his status of deficiency and become effective for the work of God. The Church must see the moral, social, cultural and material state of the nation in which it operates and on the basis of biblical and patristic experience, data or observations made in this direction by civil society or state institutions, assess how close or far find that society by God and act in order to help Christians on the path to salvation. The access of people with hearing and speech impairments to the religious services of the Orthodox Church has been one of the constant concerns of clergy. As a result of this spiritual need, Orthodox religious communities began to be established in the world for them. The word, regardless of its mode of expression, is the basis for defining man as a social being, is the essential element of communication with and from God. In the case of people with hearing and speech impairments, the word to be understood must be transformed into a sign. The language used by hearing and speech impaired believers to convey messages is sign language. The integration of the hearing-impaired into the Orthodox Church required the development of a vocabulary of religious signs through which believers could understand the Holy Mysteries. With the establishment of Orthodox christian communities of deaf people, with the establishment of parishes, the priest serving at the altar is required to use signs for all religious words, signs that help believers understand the Holy Sacraments and the catechesis. The main purpose of using this language is the full understanding of God’s word by believers.